Quantification of the degree of blending in hot-mix asphalt (HMA) with reclaimed asphalt pavement (RAP) using Energy Dispersive X-Ray Spectroscopy (EDX) analysis. (20th April 2021) - Abdalfattah, Ibrahim A.; Mogawer, Walaa S.; Stuart, Kevin
Abstract: This study quantified the degree of blending using Energy Dispersive X-Ray Spectroscopy (EDX) analyses between virgin and RAP binders inside HMA produced with RAPs from three different sources and RAP contents of 15%, 25%, and 40% by weight of the mixture. Titanium oxide (TiO2 ) nanoparticles were selected as a virgin binder tracer inside the RAP mixtures. Two different fabrication procedures were executed per RAP mixture where the first procedure simulated 100% blending and the second represented the actual blending state; then the degree of blending was found by calculating the titanium to sulfur mass ratios (Ti:S) for the two procedures. Results showed that the average degree of blending decreased with increasing RAP content and increasing RAP binder PG. The degree of blending and homogeneity between the RAP and virgin binders for the 25% RAP mixtures were slightly lower than the corresponding 15% RAP mixtures, whereas, for the high RAP content mixtures at 40%, poor and nonhomogeneous blending were found. Moreover, RAP binder with a lower PG indicated a better blending efficiency than with a higher PG. The Thermal Stress Restrained Specimen Test (TSRST) and Indirect Tensile Asphalt Cracking Test (IDEAL-CT) were performed to assess the low- and -intermediate temperature cracking resistances of the RAP mixtures, respectively, and correlate mixture performance with the microscopic analyses.